Implementation of the Carbon Tax Policy in Indonesia: Concepts and Challenges Towards Net Zero Emissions 2060 - Matheus, Juan; Delicia, Nadya Frisca; Rasji (Universitas Serang Raya, 2023)
The current increase in the earth's temperature and significant climate change have a negative impact on the sustainability of all living things. Indonesia is one of the countries that is committed to suppressing greenhouse gas production through a carbon tax policy regulated in the Law on Harmonization of Tax Regulations as a net zero emission instrument. However, until now, this carbon tax policy has not been realized by the government because it is hindered by several factors, such as unclear plans for implementing carbon tax implementation and determining effective tax rates due to limited resources and inadequate capacity. This study aims to examine the concepts and challenges of implementing a carbon tax as a net zero emission instrument after the enactment of the Tax Harmonization Law in Indonesia. The research method used is normative-juridical, with a statutory approach and a conceptual approach using secondary data obtained through library research. Based on research results, the implementation of a carbon tax in the national tax agency is considered very important and must be carried out immediately to restore environmental damage due to carbon dioxide emissions, which have been agreed to be reduced by 29% in 2030 and achieve net zero emissions in 2060. Therefore, the government needs to immediately finalize derivative regulations regarding the carbon tax mechanism and other accompanying policies so that every carbon produced can be taxed to increase national tax efficiency.